What is Public Trust in the Health System? Insights into Health Data Use - Gille, Felix (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-ND licence. This important book uses empirical evidence to explore the concept of public trust in health systems. In doing so, it provides a comprehensive contemporary explanation of public trust, how it affects health systems and how it can be nurtured and maintained as an integral component of health system governance.